Pengaruh Kompetensi SDM Dan Karakteristik Individu Terhadap Kinerja Pegawai (Studi Pada Pusat Pelatihan Kerja Daerah (PPKD) Jakarta Selatan) - Dewi Kurniawati; Nur Latifa Ramadhani; M. Nuruddin Subhan (Fakultas Ekonomi dan Bisnis Universitas Pancasila Jakarta, 2024)
This research aims to determine the influence of HR competency and individual characteristics on employee performance. The population in this study was all PPKD South Jakarta employees, totaling 44 employees and the sampling technique used a saturated sample of 44 employees. The data analysis techniques used in this research are the classical assumption test, multiple regression analysis, coefficient of determination, t test, and F test. The results of the research show that partially HR competency influences employee performance, and individual characteristics influence employee performance. And simultaneously HR competency and individual characteristics influence employee performance.